関節パンピング療法の併用により徒手整復が有効であった陳旧性顎関節脱臼の一例 - 高井, 良招; 桑島, 広太郎; 住友, 伸一郎; 毛利, 謙三; 大野, 健二 (Journal of the Japanese Society for the Temporomandibular Joint, 2005)
Chronic dislocation of the temporo-mandibular joint (TMJ) is often neglected for a long time without resetting for more than 3 or 4 weeks. In such cases, closed reduction may be very difficult because of fibrotic and/or osteogenic changes in the joint space. A twentysix-year old man was referred to our hospital complaining of long-term anterior dislocation of the TMJ. Jaw manipulation using the Hippocraes method followed by intra-articular pumping of the upper joint space of the TMJ achieved a good resetting result. 陳旧性顎関節脱臼とは関節脱臼後, 整復されず3～4週間放置され, 顎関節に器質的変化が生じ, 整復が困難になる疾患である。患者は26歳の男性。1か月半に及ぶ陳旧性顎関節前方脱臼の整復を求めて紹介来院した。徒手整復のみでの整復は不能であったが, 上関節腔のパンピング療法を施行した後に, 再度ヒポクラテス法を施行することで整復可能であった。